Parents’ Role in Supporting Their Children’s Online Learning Process - Aam Alamsyah (Universitas Pahlawan Tuanku Tambusai, 2022)
The present study examined the role of parents in supporting their children when learning through virtual means or on-line learning amid the pandemic COVID-19 outbreak. The respondents of the present study were five adults (3 males and 2 females) of different families. The study was conducted in a case study in order to allow the researchers to identify more specific data regarding the significance of parents’ role in the newly applied learning strategies as well as some potential determinants affecting their roles. The findings of the study indicate that there are some themes, which are percieved important by the parents, such as parents’ welfare, parent’s education, and time-managment. It is also found that parents’ higher education and the jobs related to pedagogy (e.g., being a teacher), can significantly help support their children learning process. Last but not least, younger ages pose more challenges to their parents as they are not really familiar with this new learning process.